Oral and Written Sources in Mark 4.1–34 - Sellew, Philip Harl (New Testament studies, 1990)
When scholars discuss the compositional processes of the Gospel of Mark, one of the important questions is the extent to which the evangelist drew on earlier sources. Mark seems to have collected and reordered a great amount of disparate material and given it his own stamp in order to produce something new. But the details of this process of collection, redaction, and composition are not at all clear. To what extent were those traditions already gathered or collected before Mark? Were the pre-Marcan materials transmitted in oral or written form? What degree of freedom did the gospel writer employ in taking over, adapting, or rewriting earlier sources?